Używki w ciąży - alcohol = Stimulants in pregnancy - alcohol - AGNIESZKA KONSTANCJA PAWŁOWSKA-MUC; CELINA ŁEPECKA-KLUSEK; ANNA PILEWSKA-KOZAK; GRAŻYNA STADNICKA (Kazimierz Wielki University, 2015)
Pawłowska-Muc Agnieszka Konstancja, Łepecka-Klusek Celina, Pilewska-Kozak Anna Bogusława, Stadnicka Grażyna. Używki w ciąży - alcohol = Stimulants in pregnancy - alcohol. Journal of Education, Health and Sport. 2015;5(8):385-394. ISSN 2391-8306. DOI10.5281/zenodo.29606 http://dx.doi.org/10.5281/zenodo.29606 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A385-394 https://pbn.nauka.gov.pl/works/614390 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.07.2015. Revised 24.08.2015. Accepted: 24.08.2015.   Używki w ciąży - alkohol Stimulants in pregnancy - alcohol   Pawłowska-Muc Agnieszka Konstancja1, Łepecka-Klusek Celina2, Pilewska‑Kozak Anna Bogusława2, Stadnicka Grażyna3   [1] Ośrodek Kształcenia Podyplomowego Pielęgniarek i Położnych Radomski Szpital Specjalistyczny im. dr Tytusa Chałubińskiego w Radomiu, ul. Lekarska 4 2 Katedra i Klinika Ginekologii i Endokrynologii Ginekologicznej Uniwersytet Medyczny w Lublinie, Al. Racławickie 23 3 Samodzielna Pracownia Umiejętności Położniczych Uniwersytet Medyczny w Lublinie, ul. Staszica 4/6 1 Postgraduate Training Centre for Nurses and Midwives, Dr Tytus Chałubiński Specialist Hospital in Radom, ul. Lekarska 4 2 Department and Clinic of Gynaecology and Gynaecological Endocrinology, School of Health Studies, Medical University of Lublin, Al. Racławickie 23 3 Independent Obstetric Skills Workshop, Medical University of Lublin, ul. Staszica 4/6   Adres do korespondencji: mgr piel. Agnieszka Konstancja Pawłowska-Muc Ośrodek Kształcenia Podyplomowego Pielęgniarek i Położnych Radomski Szpital Specjalistyczny im. dr Tytusa Chałubińskiego w Radomiu, ul. Lekarska 4 tel. 48  3615616; fax: 48 3615437 e-mail: agmich@vp.pl   Używki w ciąży - alkohol Streszczenie Wprowadzenie. Spożywanie alkoholu kobiety w wieku rozrodczym jest problemem wielu krajów świata. Stwarza ono duże zagrożenie dla ich zdrowia prokreacyjnego, prawidłowego przebiegu ciąży, zdrowia noworodka i dziecka w późniejszym okresie jego życia. Cel pracy. Celem pracy było ukazanie skali problemu oraz skutków spożywania alkoholu przez kobiety w okresie ciąży. Skrócony opis stanu wiedzy. Z przeglądu piśmiennictwa wynika, iż skala problemu jest trudna do oszacowania. Negatywnych skutków jest zdecydowanie więcej niż pozytywnych. Dotychczas nie określono jeszcze bezpiecznej dawki alkoholu dla ciężarnych, a kobiet spożywających napoje alkoholowe w tym czasie jest wciąż za duża. Świadomość konsekwencji takich zachowań nie zawsze idzie w parze z całkowitą rezygnacją z picia alkoholu podczas ciąży. Podsumowanie. Istnieje potrzeba większego niż dotychczas angażowania się pracowników medycznych (lekarzy położników i położnych) w działalność nie tylko informacyjną, lecz także edukacyjną i wspierającą.   Słowa kluczowe: alkohol, ciąża, płód, zdrowie.                                             Stimulants in pregnancy - alcohol Abstract Introduction. Alcohol consumption by women in the reproductive period is a current problem in many countries around the world. It poses a great threat to their reproductive health, the correct parturition, the health of the newborn and the child in the later part of its life. Aim. It was the aim of this work to present the scale of the problem as well as the results of women's alcohol consumption during pregnancy. Brief description of the state of the art. The review of the bibliography indicates that the scale of the problem is hard to assess. Negative effects are much more prevalent than the positive ones. A safe unit dose for pregnant women has not yet been established and the number of women consuming alcohol during this period is still too high. The awareness of the consequences of such actions is not always accompanied by complete abstinence from alcohol consumption during pregnancy. Conclusion. This calls for a greater involvement than before on the part of the medical personnel (gynaecologists-obstetricians and midwifes) in the informative but also educational and supportive activities.   Key words: ethanol, pregnancy, foetus, health.